Characterization of pollen-expressed bZIP protein interactions and the role of ATbZIP18 in the male gametophyte - Gibalová, Antónia; Steinbachová, Lenka; Hafidh, Said; Bláhová, Veronika; Gadiou, Zuzana; Michailidis, Christos; Műller, Karel; Pleskot, Roman; Dupľáková, Nikoleta; Honys, David (Plant reproduction, 2017)
KEY MESSAGE : bZIP TF network in pollen. Transcriptional control of gene expression represents an important mechanism guiding organisms through developmental processes and providing plasticity towards environmental stimuli. Because of their sessile nature, plants require effective gene regulation for rapid response to variation in environmental and developmental conditions. Transcription factors (TFs) provide such control ensuring correct gene expression in spatial and temporal manner. Our work reports the interaction network of six bZIP TFs expressed in Arabidopsis thaliana pollen and highlights the potential functional role for AtbZIP18 in pollen. AtbZIP18 was shown to interact with three other pollen-expressed bZIP TFs-AtbZIP34, AtbZIP52, and AtbZIP61 in yeast two-hybrid assays. AtbZIP18 transcripts are highly expressed in pollen, and at the subcellular level, an AtbZIP18-GFP fusion protein was located in the nucleus and cytoplasm/ER. To address the role of AtbZIP18 in the male gametophyte, we performed phenotypic analysis of a T-DNA knockout allele, which showed slightly reduced transmission through the male gametophyte. Some of the phenotype defects in atbzip18 pollen, although observed at low penetrance, were similar to those seen at higher frequency in the T-DNA knockout of the interacting partner, AtbZIP34. To gain deeper insight into the regulatory role of AtbZIP18, we analysed atbzip18/- pollen microarray data. Our results point towards a potential repressive role for AtbZIP18 and its functional redundancy with AtbZIP34 in pollen.
Keywords: Pollen development; trans-aktivátory; Dimerization; Mutagenesis, Insertional; Arabidopsis Proteins; Basic-Leucine Zipper Transcription Factors; DNA, Plant; Y2H; Trans-Activators; Recombinant Fusion Proteins; vazba proteinů; rekombinantní fúzní proteiny; dimerizace; Transcription factors; proteiny huseníčku; Regulatory network; inzerční mutageneze; bZIP; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; Pollen; pyl; DNA rostlinná; Male gametophyte; Arabidopsis; transkripční faktory bZIP; Protein Binding